Implementasi Model Perhitungan Untuk Menentukan Performa Basis Data MySQL Dan PostgreSQL - Dias Wendri, Yoga Pramuda; Kusmiran, Ari; Arman, Molavi (Program Studi Teknik Informatika Universitas Multi Data Palembang, 2022)
The Application must be can accessible for twenty-four hours a day by its users, the proper implementation and difference of databases is very important to support the connections from hundreds of thousands of users. More and more complaints from users that appear to performance, and as well as increase of the number of visits to the database applications that used MySQL and PostgreSQL to components Queries Performed: Read, Write and0 Transaction, Per-request Statistics: Average and Threads Fairness: Execution Time. In that three components is doing the test for determine which one is the best between the using of MySQL and PostgreSQL databases as well as giving the best solution in election databases which is different test components is results. This research is uses the indenpendent sample t-test calculation formula using two computers, the database used has the same size, to find out whether the differences from the result of the two databases. The result of the research is explained that MySQL is the best results compare with PostgreSQL by using indenpendent sample t-test method as the best solution.